Respuesta :

The first thing you should do is make the equation 4x+1=13 to find x. You then remove 1 from each side to get 4x=12, and then you divide by 4 to get x=3.

The next thing you do is make the equation -2y+8(3)=y+2(3)
Which simplified is -2y+24=y+6. You then add 2y to each side and remove 6 from each side to get the 18=3y. You then divide by 3 to get y=6.
Y=6
Here's how it works.
We know x=3 because 4x3+1 = 13, which is the same as the other side. 
Then if we do 2x3+6=12
And then 8x3-2x6=12
Now we know the bases are equal, therefore Y=12

Hope this helps
ACCESS MORE